Cardiovascular risk and its relationship with the lifestyle in students of the faculty of health sciences of a private university in Lima, 2017 - Zhunaula Guamán, Tania (2018)
Objective: To determine cardiovascular risk and its relationship with the lifestyle of students from the Faculty of Health Sciences of a Private University in Lima, 2017. Materials and methods: It was a quantitative, descriptive, correlational and transversal study, in which 183 students selected by non- probabilistic sampling participated. There were applied the “Healthy lifestyle” and an anthropometric data sheet. Results: From the sample population, 67.3% are women and 100% are single, 85.2% are aged between 18 and 23 years and 49.2% are from the coast. According to the labor condition, 77.6% are dependent and 50.3% are in fourth year. In the lifestyle dimension, it was found that 48.6% keep an unhealthy physical and sport condition. Also, 50.8% are healthy in recreation and free time management. 85.8% are very healthy in drug, alcohol and tobacco consumption. 66.1% are healthy in the dream dimension and 56.3% remain healthy in eating habits. 55.7% are unhealthy in self-care and medical care. It was not found a statistically significant relationship between CVR and healthy lifestyle (p=0.234). Eating habits have a statistically significant relationship with CVR (p=0.012). Conclussion: We conclude that 82% of the students are healthy and 54% presented a moderate cardiovascular risk. It was not found a statistically significant correlation between CVR and lifestyle (p=0.234), nevertheless it was found a correlation between CVR and eating habits (p=0.012).